Update of Perinatal Human Immunodeficiency Virus Type 1 Transmission in France: Zero Transmission for 5482 Mothers on Continuous Antiretroviral Therapy From Conception and With Undetectable Viral Load at Delivery. (29th August 2022) - Sibiude, Jeanne; Le Chenadec, Jérôme; Mandelbrot, Laurent; Hoctin, Alexandre; Dollfus, Catherine; Faye, Albert; Bui, Eida; Pannier, Emmanuelle; Ghosn, Jade; Garrait, Valerie; Avettand-Fenoel, Véronique; Frange, Pierre; et al.
Abstract: Background: Antiretroviral therapy (ART) is remarkably effective in preventing perinatal transmission (PT) of HIV-1. We evaluated the PT rate in a population of women with widespread access to ART before conception. Methods: The analysis included 14 630 women with HIV-1 who delivered from 2000 to 2017 at centers participating in the nationwide prospective multicenter French Perinatal Cohort (ANRS-EPF). PT was analyzed according to time period, timing of ART initiation, maternal plasma viral load (pVL), and gestational age at birth. No infants were breastfed, and all received neonatal prophylaxis. Results: PT decreased between 3 periods, from 1.1% in 2000–2005 (58/5123) to 0.7% in 2006–2010 (30/4600) and to 0.2% in 2011–2017 (10/4907; P < .001). Restriction of the analysis to the 6316/14 630 (43%) women on ART at conception, PT decreased from 0.42% (6/1434) in 2000–2005 to 0.03% (1/3117) in 2011–2017 ( P = .007). Among women treated at conception, if maternal pVL was undetectable near delivery, no PT was observed regardless of the ART combination [95%CI 0-0.07] (0/5482). Among women who started ART during pregnancy and with undetectable pVL near delivery, PT was 0.57% [95%CI 0.37-0.83] (26/4596). Among women treated at conception but with a detectable pVL near delivery, PT was 1.08% [95%CI 0.49-2.04] (9/834). We also qualitatively described 10 cases of transmission that occurred during the 2011–2017 period. Conclusions: In a setting with free access to ART, monthly pVL assessment, infant ART prophylaxis, and in the absence of breastfeeding, suppressive ART initiated before pregnancy and continued throughout pregnancy can reduce PT of HIV to almost zero. Abstract : Among 5482 women living with human immunocompromised virus treated at conception, with viral suppression at delivery, not breastfeeding, and with infant prophylaxis for all, no case of perinatal transmission was observed (0 of 5482, 95% confidence interval, 0–.07).